ANALISIS KECURANGAN LAPORAN KEUANGAN : PENGUJIAN TEORI FRAUDDIAMOND (STUDI PADA PERUSAHAAN MANUFAKTUR DI INDONESIA) - Fahmi Rizani; Rasidah; Riyanda Putra (Universitas Lambung Mangkurat, 2019)
This study aims to determine the factors that influence fraud in financial statements. Detection of fraudulent financial statements using the theory of Fraud Diamond in manufacturing companies listed on the Indonesia Stock Exchange in 2016-2017. Fraud Diamond proposed by Wolfe and Hermanson (2009). Four variables of fraud diamond were tested which consisted of pressure, opportunity, rationalization and competency. Pressure is proxied by financial targets, financial stability, external pressures and individual financial needs. Opportunities are proxied by the effectiveness of supervision and the nature of the industry. Rationalization is proxied by the change of auditors, and Competency (capability) is proxyized by the replacement of the board of directors. The research sample used was 70 manufacturing companies listing on the Indonesia Stock Exchange in the 2016-2017 period with 140 financial statements. Data were analyzed using logistic regression analysis. The results showed that the variables financial targets, financial stability, external pressures, individual financial needs of supervision, ineffective monitoring, the nature of the industry, change of auditors and changes in the board of directors did not have an influence on financial statement fraud. From the results of these studies indicate that all research variables studied at each manufacturing company have not been able to indicate financial statement fraud.